Theoretical Neuropsychological Construction of Executive Functions - Coello-Zambrano, Emily (2022)
Executive functions (EF) constitute a large conglomerate of cognitive abilities that, as their name indicates, carry out decisive actions in decision-making and human behavior. They are of a cognitive and socio-emotional nature, they coordinate the input and output information to regulate the behaviors, thoughts, and emotions of a task to be performed. Alexander Luria raises its conceptualization at the beginning of the seventies, being Muriel Lezak the one in charge of its scientific dissemination. In this article, a bibliographic compilation on EFs, their best known theoretical models, their neuropsychological evaluation process, the most common disorders and the most relevant studies in recent years is made.